Educating for Cultural Survival in Nunavut: Why Haven’t We Learned from the Past? - McMillan, Barbara (Paideusis, 2015)
This is a paper about the culture of the Inuit in the Nunavut Territory of the Canadian Arctic, and the role that education should take in preventing its slow dilution, demise, and loss. The measures to be taken are evident. Inuit philosophy (Inuit Qaujimajatuqangit) must be the framework, and Inuit must be in control, not only of policy and curricula, but also of the school system, the schools, and the classrooms. It can take decades for outsiders embedded in a different culture to communicate and see through an unfamiliar worldview. Inuit do not have the luxury of time to wait for this to happen. Non-Inuit need to understand what Inuit are saying, to appreciate what they aim to achieve, and then get out of the way. If this is not done, the Inuit culture will go the way of so many other Indigenous cultures that once flourished. It’s inconceivable that we non-Inuit Canadians are willing not only to watch this happen but continue to be the cause.